A New Approach to Constrain the Seismic Origin for Prehistoric Turbidites as Applied to the Dead Sea Basin. Issue 3 (4th February 2021) - Lu, Yin; Moernaut, Jasper; Bookman, Revital; Waldmann, Nicolas; Wetzler, Nadav; Agnon, Amotz; Marco, Shmuel; Alsop, G. Ian; Strasser, Michael; Hubert‐Ferrari, Aurélia
Abstract: The seismic origin of turbidites is verified either by correlating such layers to historic earthquakes, or by demonstrating their synchronous deposition in widely spaced, isolated depocenters. A historic correlation could thus constrain the seismic intensity required for triggering turbidites. However, historic calibration is not applicable to prehistoric turbidites. In addition, the synchronous deposition of turbidites is difficult to test if only one deep core is drilled in a depocenter. Here, we propose a new approach that involves analyzing the underlying in situ deformations of prehistoric turbidites, as recorded in a 457 m‐long core from the Dead Sea center, to establish their seismic origin. These in situ deformations have been verified as seismites and could thus authenticate the trigger for each overlying turbidite. Moreover, our high‐resolution chemical and sedimentological data validate a previous hypothesis that soft‐sediment deformation in the Dead Sea formed at the sediment‐water interface. Plain Language Summary: Seismogenic turbidites are widely used for geohazard assessment. The use of turbidites as an earthquake indicator requires a clear demonstration that an earthquake, rather than non‐seismic factors, is the most plausible trigger. The seismic origin is normally verified either by correlating the turbidites to historic earthquakes, or by demonstrating their synchronous deposition in widely spaced, isolated depocenters. The correlated historic earthquakes could thus constrain the seismic intensities necessary for triggering turbidites. However, the historic correlation method is not applicable to prehistoric turbidites. In addition, the synchronous deposition of turbidites cannot be verified if only one deep core is drilled in a depocenter. Here, we propose a new approach to constrain the seismic origin for prehistoric turbidites in a deep core from the Dead Sea center. Moreover, we constrain the seismic intensities that triggered prehistoric turbidites by analyzing the degree of in situ deformation underlying each turbidite. In addition, we use our results to propose seven basic earthquake‐related depositional scenarios preserved in depocenters located in tectonically active regions like the Dead Sea. These techniques and findings permit a more confident geohazard assessment in the region and other similar tectonic settings by improving the completeness of a paleoseismic archive. Key Points: Seismic origin for prehistoric turbidites is established by analyzing the underlying in situ deformation structures for each turbidite Data validate a previous hypothesis that soft‐sediment deformation formed at the sediment‐water interface in the Dead Sea The new approach permits a more confident geohazard assessment by improving the completeness of a paleoseismic archive